Numerical Modeling and Simulation of Wave Impact of a Circular Cylinder during the Submergence Process. (3rd December 2017) - Hu, Xiaozhou; Jiang, Yiyao; Cai, Daojun
Abstract : Wave slamming loads on a circular cylinder during water entry and the subsequence submergence process are predicted based on a numerical wave load model. The wave impact problems are analyzed by solving Reynolds-Averaged Navier-Stokes (RANS) equations and VOF equations. A finite volume approach (FV) is employed to implement the discretization of the RANS equations. A two-dimensional numerical wave tank is established to simulate regular ocean waves. The wave slamming problems are investigated by deploying a circular cylinder into waves with a constant vertical velocity. The present numerical method is validated using other numerical or theoretical results in accordance with varying free surface profiles when a circular cylinder sinks in calm water. A numerical example is given to show the submergence process of the circular cylinder in waves, and both free surface profiles and the pressure distributions on the cylinder of different time instants are obtained. Time histories of hydrodynamic load on the cylinder during the submergence process for different wave impact angles, wave heights, and wave periods are obtained, and results are analyzed in detail.